UJI AKTIVITAS TABIR SURYA FORMULA SEDIAAN LOSIO EKSTRAK METANOL DAUN MANGKOKAN (Nothophanax scutellarium Merr.) - Suryani Suryani; Rini Hamsidi; Nurlena Ikawati; Ahmad Zaeni; Hasnawati Hasnawati (Halu Oleo University, 2014)
Leaves of mangkokan (Nothophanax scutellarium Merr.) contain a potent antioxidant and sunscreen compounds. This plant potential to be developed into cosmetic products. One of cosmetic product that can be developed using natural product is lotion. This research aims to formulate lotion from methanol extracts of leaves mangkokan and determining the sunscreen activity of lotion with various concentration of the extract 1%; 2.5%; 5%; 7.5%; and 10% using laboratory experimental design. Preparation of mangkokan leaf extracts using methanol solvent by maceration method. Further tests conducted to determine the activity of sunscreen. Methanol extract of the leaves mangkokan then formulated to be lotion. Sunscreen activity of lotion was tested by determaining SPF values. Lotion methanol extract of leaves mangkokan resulting the highest SPF value contained in the methanol extract of the leaves mangkokan concentration of 10%. Keywords: mangkokan leaves, lotion, extract, lotion, sunscreen